Adherence to secondary preventive treatment following myocardial infarction with and without obstructive coronary artery disease. - Anna M Nordenskjöld; Miriam Qvarnström; Björn Wettermark; Bertil Lindahl (PLoS ONE)
Background Secondary preventive medications following myocardial infarction (MI) reduce the risk of new cardiovascular events. Discontinuation and suboptimal adherence are common and affect prognosis. However, there is limited knowledge regarding adherence in patients with myocardial infarction with non-obstructive coronary arteries (MINOCA). We therefore aim to evaluate the adherence to guideline recommended medications in patients with MINOCA and myocardial infarction with obstructive coronary arteries (MI-CAD). Methods This was a Swedish nationwide observational study of MI patients recorded in the SWEDEHEART registry between 2006─2017. A total of 9,138 MINOCA and 107,240 MI-CAD patients were followed for a mean 5.9 years. Initiation of therapy, implementation determined using medication possession ratio, and persistence rates during different time periods were calculated. Results Patients with MINOCA were less frequently prescribed secondary preventive medications than MI-CAD. The percentage of patients taking medication as prescribed were lower in MINOCA than in MI-CAD at all time points; during months 6─12 after discharge: aspirin 94.8% vs 97.2% (p < 0.001), statins 90.3% vs 94.7% (p < 0.001), and ACEI/ARBs 97.7% vs 98.5% (p = 0.002) and at 12 months: aspirin 84.4% vs 93.7% (p < 0.001), statins 83.8% vs 94.8% (p < 0.001), ACEI/ARBs 85.0% vs 92.2% (p < 0.001) and beta blockers 80.4% vs 89.6% (p < 0.001). Conclusion The rates of initiation, implementation, and persistence of secondary preventive medications were high in both MINOCA and MI-CAD patients during the first 5 years after MI. The lower rates in patients with MINOCA may be partially due to uncertainties regarding the diagnosis of MINOCA, differences in patient characteristics, and psychosocial factors. Suboptimal medical adherence in patients with MINOCA may adversely affect prognosis as previously demonstrated in MI-CAD patients.